(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Dengue fever is a major mosquito-borne viral illness in children with a wide clinical spectrum ranging from mild febrile illness to severe dengue hemorrhagic fever and dengue shock syndrome. Early identification of severe disease using clinical and laboratory parameters such as platelet count and coagulation profile is essential to reduce morbidity and mortality. Methodology: This hospital-based observational study was conducted in the Department of paediatrics Sree Mookambika Institute of Medical Sciences, Kulasekharam, from May 2025 to February 2026. Children aged 0–18 years with confirmed dengue infection (NS1 antigen/IgM/IgG positive) were included. Detailed clinical history, examination findings, complete blood count, and coagulation profile were recorded. Data were analyzed using SPSS version 17.0, and statistical significance was assessed using Chi-square test, Fisher’s exact test, unpaired t-test, and Mann–Whitney U test. Results: A total of 50 pediatric patients were studied. Most cases were observed in children >10 years (36%) with male predominance (56%). Fever was the most common symptom (98%), followed by nausea (62%) and headache (42%). Thrombocytopenia was present in 66% of patients, while leukocyte abnormalities were seen in 88%. PT and INR derangements were observed in 8% and 6% of cases respectively. Conclusion: Dengue in children presents with varied clinical manifestations, with thrombocytopenia showing a strong association with disease severity. Early monitoring of platelet count and coagulation profile is essential for timely identification of severe dengue and improved outcomes.